Detection and enumeration of vibrio parahaemolyticus in raw salad vegetables at pre-harvest level, retail level and domestic kitchen level - Maccena, Jayan (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The aim of this study was to detect and enumerate Vibrio parahaemolyticus, the leading cause ofgastroenteritis illness in human, from raw salad vegetables at pre-harvest level, retail level and domestic kitchen level in Kuching, Sarawak. In this study, a combination of Most Probable Number supplemented with Polymerase Chain Reaction method were applied to detect the presence of Vibrio parahaemolyticus, harboring the toxR gene and to enumerate their density in the samples. Based on the real event in the domestic kitchen, stimulation was designed and conducted to result a useful data and infonnation from the consumption of raw salad vegetables. With the MPN supplemented with PCR technique, out of 360 samples, none of them were detected to carry the toxR gene. However, the result highlighted that the consumption of raw salad vegetables can be a transmission route for V. parahaemolyticus; this can possess risks to the consumers.